Grain yield gains and associated traits in tropical x temperate maize germplasm under high and low plant density - Ndou, V.; Gasura, P.; Chivenge, Pauline P.; Derera, J. (Springer, 2021)
Development of ideal breeding and crop management strategies that can improve maize grain yield under tropical environments is crucial. In the temperate regions, such yield improvements were achieved through use of genotypes that adapt high plant population density stress. However, tropical germplasm has poor tolerance to high plant population density stress, and thus it should be improved by temperate maize. The aim of this study was to estimate the genetic gains and identify traits associated with such gains in stable and high yielding temperate x tropical hybrids under low and high plant population densities. A total of 200 hybrids derived from a line x tester mating design of tropical x temperate germplasm were developed. These hybrids were evaluated for grain yield and allied traits under varied plant population densities. High yielding and stable hybrids, such as 15XH214, 15XH215 and 15XH121 were resistant to lodging and had higher number of leaves above the cob. The high genetic gains of 26% and desirable stress tolerance indices of these hybrids made them better performers over check hybrids under high plant population density. At high plant population density yield was correlated to stem lodging and number of leaves above the cob. Future gains in grain yield of these hybrids derived from temperate x tropical maize germplasm can be achieved by exploiting indirect selection for resistance to stem lodging and increased number of leaves above the cob under high plant density conditions.